Differentiation, ageing and leukaemia alter the metabolic profile of human bone marrow haematopoietic stem and progenitor cells - Lalioti, Maria-Eleni; Romero-Mulero, Mari Carmen; Karabacz, Noémie; Mess, Julian; Demollin, Helen; Rettkowski, Jasmin; Schuldes, Konrad; Mitterer, Michael; Wadle, Carolin; Shoumariyeh, Khalid; Egg, Mirijam; Alfonso-Gonzalez, Carlos; et al. (Nature cell biology, 2025)
Metabolic cues are crucial for regulating haematopoietic stem and progenitor cells (HSPCs). However, the metabolic profile of human HSPCs remains poorly understood due to the limited number of cells and the scarcity of bone marrow samples. Here we present the integrated metabolome, lipidome and transcriptome of human adult HSPCs (lineage−, CD34+, CD38−) upon differentiation, ageing and acute myeloid leukaemia. The combination of low-input targeted metabolomics with our newly optimized low-input untargeted lipidomics workflow allows us to detect up to 193 metabolites and lipids from a starting material of 3,000 and 5,000 HSPCs, respectively. Among other findings, we observe elevated levels of the essential nutrient choline in HSPCs compared with downstream progenitors, which decline upon ageing and further decrease in acute myeloid leukaemia. Functionally, we show that choline supplementation fuels lipid production in HSPCs and enhances stemness. Overall, our study provides a comprehensive resource identifying metabolic changes that can be utilized to promote and enhance human stem cell function.
Online veröffentlicht: 15. Juli 2025
Gesehen am 11.09.2025